Implementasi POAC Fungsi Manajemen Pada Administrasi Keuangan Di Kantor Kecamatan Marisa Kabupaten Pohuwato - Widya Kurniati Mohi; Ramlah Alkatiri; Muh. Firyal Akbar; Isna S Baruadi (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
ABSTRACT This study aims to obtain information about the Implementation of Financial Administration at the Marisa Sub-District Office in Pohuwato Regency. The research method uses a qualitative type. Data collection techniques are done through interviews with a number of informants and observations and recording of secondary data related to research problems. The results of the study concluded that the implementation of financial administration in the planning, organizing, movement and supervision phases has not been effectively seen from human sources not professional in planning activities and budgeting, incompatibility of main tasks/function and preparation of LPJ and internet network systems which are obstacles in the reporting process. So it is expected that the government optimizes the implementation of financial administration by conducting education and training on financial administration management and increasing supervision and control. Keywords                   : Implementation; Financial Administration  ABSTRAKPenelitian ini bertujuan memperoleh informasi tentang Pelaksanaan Administrasi Keuangan di Kantor Camat Marisa Kabupaten Pohuwato. Metode penelitian menggunakan jenis kualitatif. Teknik pengumpulan data dilakukan melalui wawancara dengan sejumlah informan dan observasi serta pencatatan data sekunder yang berkaitan dengan permasalahan penelitian. Hasil penelitian menyimpulkan bahwa pelaksanaan administrasi keuangan dalam tahap perencanaan, pengorganisasian, pergerakan dan pengawasan belum efektif dilihat dari  sumber manusia belum profesional dalam merencanakan kegiatan dan penganggaran, ketidak sesuaian tupoksi dan  penyusunan LPJ  serta sistem jaringan internet yang menjadi kendala dalam proses pelaporan. Maka diharapkan kepada pemerintah mengoptimalkan pelaksanaan  administrasi keuangan dengan mengadakan pendidikan dan pelatihan tentang pengelolaan administrasi keuangan serta meningkatkan pengawasan dan pengontrolan. Kata Kunci                 : Pelaksanaan; Administrasi Keuangan